2018
DOI: 10.1002/slct.201701841
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Catalytic Oxidation of Ethylbenzene to Acetophenone by Metallophthalocyanine Intercalated Layered Double Hydroxide with Oxygen

Abstract: The organic‐inorganic hybrid material originated from metallophthalocyanine and layered double hydroxide has been identified as bifunctional catalyst for the oxidation of ethylbenzene to acetophenone. The hybrids exhibited excellent catalytic activity in the selective oxidation through O2/NHPI (N‐hydroxyphthalimide) system with excellent selectivity of acetophenone. The hybrid could accelerate not only the formation of hydroperoxide, but also the decomposition of hydroperoxide. Further, the catalyst also exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Raising the temperature (160 o C) favours for the production of higher amount of oxygen radicals which caused considerable enhancement in conversion but the reduces the selectivity of acetophenone due to over oxidation. 57 Nevertheless, with further increase of reaction time at 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 25 corresponding oxidation products at moderate conversions ( Table 3, entry 3). Comparison of conversion rate for the tetralin and indane, among these indane has shown high catalytic oxidation to respected oxidized products due to C-H low bond dissociation energy (82.9 K cal /mole) and high strained C-H bond compared to the tetralin molecule, further confirming the broader applicability of our catalysts for the selective oxidation of saturated C-H bonds.…”
Section: Resultsmentioning
confidence: 94%
“…Raising the temperature (160 o C) favours for the production of higher amount of oxygen radicals which caused considerable enhancement in conversion but the reduces the selectivity of acetophenone due to over oxidation. 57 Nevertheless, with further increase of reaction time at 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 25 corresponding oxidation products at moderate conversions ( Table 3, entry 3). Comparison of conversion rate for the tetralin and indane, among these indane has shown high catalytic oxidation to respected oxidized products due to C-H low bond dissociation energy (82.9 K cal /mole) and high strained C-H bond compared to the tetralin molecule, further confirming the broader applicability of our catalysts for the selective oxidation of saturated C-H bonds.…”
Section: Resultsmentioning
confidence: 94%
“…A plausible mechanism for this catalytic process was proposed, which involved deprotonation and radical pathways. Chen and collaborators [79] found that the hybrid materials M(II)Pc(SO3 -)4@-Zn2Al-LDH (M = Co(II), Cu(II), Mn(II), and Fe(II)), obtained from the coprecipitation method of the metal complexes of the anionic tetrasulfonic phthalocyanine M(II)Pc(SO3H)4 (Figure 17) with zinc and aluminum layered double hydroxides (LDHs) showed an excellent catalytic performance in the oxidation of different olefins in the presence of O2/isobutyraldehyde, IBA [80] and are also efficient catalysts for the selective oxidation of ethylbenzene to acetophenone in the presence of O2/NHPI (N-hydroxyphthalimide), using benzonitrile as solvent at 120 °C. The best results were observed for the hybrid M = Co(II) (90% of conversion and selectivity higher than 99%) with no appreciable reduction on its activity or selectivity even after five runs.…”
Section: Figure 24mentioning
confidence: 99%
“…Under the optimized reaction conditions, M(II)Pc(SO3 − )4@-Zn2Al-LDH was also able to catalyze the aerobic oxidation of other alkyl arenes (Table 4) and a series of controlled experiments suggested that a synergistic effect might exist between the basicity of the support and the activity of M(II)Pc during the oxidation. Chen and collaborators [79] found that the hybrid materials M(II)Pc(SO 3 − ) 4 @-Zn 2 Al-LDH (M = Co(II), Cu(II), Mn(II), and Fe(II)), obtained from the coprecipitation method of the metal complexes of the anionic tetrasulfonic phthalocyanine M(II)Pc(SO 3 H) 4 (Figure 17) with zinc and aluminum layered double hydroxides (LDHs) showed an excellent catalytic performance in the oxidation of different olefins in the presence of O 2 /isobutyraldehyde, IBA [80] and are also efficient catalysts for the selective oxidation of ethylbenzene to acetophenone in the presence of O 2 /NHPI (N-hydroxyphthalimide), using benzonitrile as solvent at 120 • C. The best results were observed for the hybrid M = Co(II) (90% of conversion and selectivity higher than 99%) with no appreciable reduction on its activity or selectivity even after five runs. Under the optimized reaction conditions, M(II)Pc(SO 3 − ) 4 @-Zn 2 Al-LDH was also able to catalyze the aerobic oxidation of other alkyl arenes (Table 4) and a series of controlled experiments suggested that a synergistic effect might exist between the basicity of the support and the activity of M(II)Pc during the oxidation.…”
Section: Figure 24mentioning
confidence: 99%
“…immobilized metalloporphyrins and their catalysis systems [31][32][33][34][35] adapting to the cleaner production process. However, the resulting yields (acetophenone and phenylethanol (ONE + OL), less than 25%) were lower than those obtained from the catalytic systems above [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . In addition, RSM was also seldom used in the catalytic field of metalloporphyrins [14][15][16][17]19,20,[31][32][33][34][35] .…”
mentioning
confidence: 75%